PEMBUATAN MAJALAH PEMBELAJARAN BAGI ANAK – ANAK - Amanda Rosetia; Renny Christiarini; Nur Hidayati; Yongkie Yongkie; La Ode Agung Prastiyo; Muhammad Dimas Pramudya; Alfrets Yohanes Kodoatie; Winson Leon; Krisnayanti Krisnayanti; Edi Tan Sopian; Lili Yanti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2020)
From the results of a survey of children we have done, the most vital issue of the topic of humanity in children is about access to education and equal opportunities to explore their potential. Therefore we agreed to Society Empowerment Program (SEPORA) project for neglected children by making a children's learning magazine that can be consumed at any time, of course, packaged with as attractive as possible. The children’s learning magazine called Nusantara, with the content about nationalism. Hopefully that they will be helped with literacy access and of course hopefully they will be motivated by the contents of the magazine.